A cluster analysis of the relationship between sucking habits, consistency of food ingested, and taste sensitivity in children. Issue 3 (4th April 2019) - Marquezin, Maria Carolina S.; Araujo, Darlle S.; Amato, Juliana N.; de S. Barbosa, Taís; Fonseca, Fernando L. A.; Gavião, Maria B. D.; Castelo, Paula Midori
Abstract: As sucking habits and eating behavior may be interrelated and also associated with taste, body composition, and sociodemographic factors, the objective was to perform an exploratory analysis to identify groups of children with a high degree of association between intragroup subjects, providing explanation and interpretation of the data. The study initially included 352 prepubertal children (197 girls; 7‐ to 11‐year‐old), from whom information about sociodemographic characteristics, duration of breastfeeding, past bottle‐feeding and non‐nutritive sucking habits, taste sensitivity, body mass index (BMI), and consistency of food ingested were collected. Salivary concentrations of amylase and total protein were also determined. Data were submitted to cluster analysis (hierarchical analysis, K ‐means, and silhouette plot), one‐way ANOVA and correlation tests. Cluster analysis included 159 children, generating three reliable and meaningful clusters: Cluster 1 (labeled "good tasters"), was characterized by older children and higher taste sensitivity; Cluster 2 ("softer food consistency") by longer bottle‐feeding duration and children who eat food with lower consistency, and Cluster 3 ("breastfed") by longer breastfeeding duration (silhouette coefficient = 0.61). Cluster 3 also showed the higher percentage of normal‐weight children, normal delivery, maternal schooling, and lower rate of past non‐nutritional sucking habit. No correlation was found between salivary amylase and total protein concentrations, taste sensitivity and BMI, although taste sensitivity showed to be higher among girls ( p = 0.002; power = 88%). The study identified three clusters, highlighting the relationship between nutritional sucking habits, consistency of food ingested, and sociodemographic characteristics. Most importantly, a close relation between bottle‐feeding and consumption of soft food consistency was observed.